Agapetes malipoensis S. H. Huang (Ericaceae juss. ), a new species for the flora of Vietnam - Thanh Huong, Nguyen Thi; Hiep, Nguyen Tien (Academia Journal of Biology, 2012)
In the world, the genus Agapetes D. Don ex G. Don (Ericaceae Juss.) had about 95 species, throughout the trop. Asia to Western Pacific. At present, 5 native Agapetes species were collected in Vietnam. During the time to study specimen on this genus in Hanoi herbarium, we found one new species Agapetes malipoensis S.H. Huang. It was a new record for the flora of Vietnam. Thus there are 6 species belonging to the genus Agapetes D. Don recorded for the flora of Vietnam. It has some especial characters as epiphyte shrubs; rootstock spindle-shaped; twigs cylindrical, densely brown spreading glandular setose. Leaves pseudoverticillate or opposite; petiole 1-3 mm; leaf blade elliptic or oblong-lanceolate 6.5-11 ´ 2.2-3.7 cm, margin plane, entire. Inflorescences fasciculate in axil of leaves, usually 3-4 flowered; pedicel 3-6 mm, densely glandular setose or galbrous. Corolla white, tubular, 2cm. Filaments 1.4 cm; with a pair of spurs on the top, ca 2 mm. Berry globose, ripe purple-red, 4 mm in diam, setose. This species has been discovered from the Lai Chau, Cao Bang, Ha Giang and Lao Cai provinces, adjacent with the local type in the Yunnan province, China. Its specimens were deposited in the Herbarium of the Institute of Ecology and Biological resources, Hanoi, Vietnam (HN).